Alloreactivity: the Janus-face of hematopoietic stem cell transplantation - Gratwohl, Alois; Dreger, Peter (Leukemia, 2017)
Differences in major and minor histocompatibility antigens between donor and recipient trigger powerful graft-versus-host reactions after allogeneic hematopoietic stem cell transplantation (HSCT). The clinical effects of alloreactivity present a Janus-face: detrimental graft-versus-host disease increases non-relapse mortality, beneficial graft-versus-malignancy may cure the recipient. The ultimate consequences on long-term outcome remain a matter of debate. We hypothesized that increasing donor-recipient antigen matching would decrease the negative effects, while preserving antitumor alloreactivity. We analyzed retrospectively a predefined cohort of 32 838 such patients and compared it to 59 692 patients with autologous HSCT as reference group. We found a significant and systematic decrease in non-relapse mortality with decreasing phenotypic and genotypic antigen disparity, paralleled by a stepwise increase in overall and relapse-free survival (Spearman correlation coefficients of cumulative excess event rates at 5 years 0.964; P<0.00; respectively 0.976; P<0.00). We observed this systematic stepwise effect in all main disease and disease-stage categories. The results suggest that detrimental effects of alloreactivity are additive with each step of mismatching; the beneficial effects remain preserved. Hence, if there is a choice, the best match should be donor of choice. The data support an intensified search for predictive genomic and environmental factors of ‘no-graft-versus-host disease’.
Gesehen am 03.05.2018